Development of Instrument Performance Self-Efficacy Scale Çalgı Performansına İlişkin Öz-Yeterlik Ölçeğinin geliştirilmesi - Şeker, Sadullah Serkan (Journal of Human Sciences, 2016)
The aim of this study is to develop a valid and reliable scale that can be used in determining preservice music teacher’s self-efficacy beliefs towards instrumental performance. The first step of this study is to get an expert view about items. After this process the scale was administrated 443 preservice music teachers and explanatory factor analysis was applied. According to EFA results, the scale was consisted of three sub-dimensions that are called “self-efficacy towards instrumental performance”, “negative emotions felt in instrumental practicing” and “modeling”. The cronbach alpha coefficients of this three sub dimension are found, 85 for the first factor, 82 for second factor and, 76 for third factor. The scale along with its three sub-dimensions are accounted for 52,5 percent of total variance. After EFA, DFA was applied for new data set that was consisted of 275 preservice teachers. According to DFA results, it is understood that the model showed great fit (x2 = 283.52, DF =148). After DFA, convergent validity was applied using “Self-efficacy beliefs toward instrumental performance scale developed by Girgin (2015). Correlation coefficient (r=65, p<0,01) shows that those two scales show high convergence each other. The last stage in the developmental process is test re-test analysis. For this analysis scale was administrated same group (n=68) 17 days apart. The correlation coefficient shows that the scale shows high consistency when it was administrated different time periods (r= 88, p<0,01). Özet Bu çalışmanın amacı eğitim fakültesi güzel sanatlar eğitimi bölümü müzik eğitimi anabilim dallarında öğrenim görmekte olan öğretmen adaylarının çalgısal performanslarına ilişkin öz-yeterlik düzeylerinin belirlenmesine yönelik geçerli ve güvenilir bir ölçme aracı geliştirmektir. Ölçek geliştirilme aşamasında öncelikle uzman görüşüne başvurulmuş ön deneme formu hazırlandıktan sonra 443 kişilik katılımcı grubuna uygulanarak açımlayıcı faktör analizi yapılmıştır. Açımlayıcı faktör analizi sonucunda ölçeğin “çalgı performansına yönelik öz-yeterlik inancı”, “çalgı çalışma sırasında hissedilen negatif duygular” ve “model alma” olmak üzere üç alt boyuta sahip olduğu görülmüş, üç alt boyutun total varyansın % 52,5’ini açıkladığı belirlenmiştir. Ölçek maddelerinin faktör yükleri ,45 ile ,98 arasında değişmektedir. Ölçeğin iç geçerlik katsayıları incelendiğinde ise “çalgı performansına yönelik öz-yeterlik inancı”nın ,85, “çalgı çalışma sırasında hissedilen negatif duygular”ın ,82 ve “model alma” alt boyutunun ise ,76 olduğu tespit edilmiştir. Ölçeğe yapılan doğrulayıcı faktör analizi sonucunda oluşturulan modelin x2 = 283.52 df=148 olduğu tespit edilmiş x2/df oranının (1,91) modelin iyi uyum sergilediğini temsil ettiği görülmüştür. Geliştirilen ölçeğin daha sonra benzer ölçek geçerliği analizleri yapılmış ve her iki ölçeğin toplam puanlarına ilişkin pozitif yönde kuvvetli ilişki gösterdiği (r=,651, p<0,01) görülmüştür. son olarak ölçeğe test-tekrar test uygulanmış ve 17 gün arayla ölçeğin yüksek tutarlık gösterdiği görülmüştür (r= ,88, p<0,01).